0121 Home Care Worker Ergonomic Hazards. (23rd June 2014) - Tendick Matesanz, Felipe; Thomason, Jane; Love, Marsha; Zanoni, Joseph
Abstract : Objectives: Home care workers (HCW) are at high risk of musculoskeletal disorders related to consumer care and housekeeping tasks and need of ergonomic interventions (Arlinghaus, et al ., 2013; Baron and Habes, 2004; Hodsonetal et al ., 2010). The goal of this project is to explore HCW experiences and perceptions to document potentially hazardous tasks to inform intervention and policy. Method: In 2012 researchers partnered with a labour union (SEIU) representing HCWs to recruit those with at least 3 years of experience with consumers needing moving assistance. Forty six mostly African Americans participated in four focus groups and a validation session. Participants were asked to review a listing of common tasks, describe which tasks resulted in pain, and share tips for injury prevention. Results: Themes identified through content analysis of transcripts include: a) Care giving relationship--The approach that HCWs take toward their consumers impacts the consumers' behaviours and may reduce injury risks, b) Exchanging information--HCWs want to learn about consumer conditions and assistive devices/practices to help mitigate pain and improve mobility and c) Problem solving about devices/practices--HCWs have a stake in introducing devices, educating and negotiating with consumers to impact their movement and care. Conclusions: In summary, CHWs have insights into their work and should be supported to 1) identify risky tasks, 2) to document barriers and solutions to implement them, 3) to share resources and 4) to identify training needs. The findings may be explored in labour-management forums in order to create policies and procedures to reduce ergonomic risks to HCWs and their consumers.